Anatomy of the pulp chamber and the root canal system: Pedagogical strategies A literature review - Restrepo Salas, Ivan Felipe; Alfonso Morales , Gilbert (Revista Estomatología, 2023)
ABSTRACT Background: Anatomical knowledge of the pulp chamber and the root canal system is essential for correct diagnosis and treatment planning in endodontics. The pedagogical tools aimed at dental students as support in the training processes of the endodontics subject favor the appropriation of knowledge and identification of the morphological variants of the root canal system, which allow the student the integration of knowledge. Objective: To identify, through a review of the literature, the pedagogical strategies used to teach morphology of the root canal system in endodontics. Method: A bibliographic search of original studies was carried out in the Medline (Pubmed), SciELO, Lilacs, Medline (Ovid), Web of Science, Scopus, Embase, and Google academic databases, choosing studies published from 2010 to 2022. , for the selection of the definitive articles, studies concerning pedagogical processes in endodontics were selected, thus excluding other types of approaches in the area of ​​dentistry. Results: A total of 63 references were identified, 16 of which were analyzed and selected, 47 being excluded for not meeting the inclusion criteria. Conclusion: The use of virtual, didactic and technological pedagogical tools favor a positive effect on the dentistry undergraduate student while learning the anatomy of root canal systems that increase confidence and security when performing endodontic treatment in patients.